Determinants of Neural Plastic Changes Induced by Motor Practice - Dai, Wen; Nakagawa, Kento; Nakajima, Tsuyoshi; Kanosue, Kazuyuki (Frontiers in Human Neuroscience, 2021)
Short-term motor practice leads to plasticity in the primary motor cortex (M1). The purpose of this study is to investigate the factors that determine the increase in corticospinal tract excitability after motor practice, with special focus on two factors; “the level of muscle activity” and “the presence/absence of a goal of keeping the activity level constant”. Fifteen healthy subjects performed four types of rapid thumb adduction in separate sessions. In the “comfortable task” (C) and “forceful task” (F), the subjects adducted their thumb using comfortable and strong forces. In the “comfortable with a goal task” (CG) and “forceful with a goal task” (FG), subjects controlled the muscle activity at the same level as in the C and F, respectively, by adjusting the peak electromyographic amplitude within target ranges. Paired associative stimulation (PAS), which combines peripheral nerve (median nerve) stimulation and transcranial magnetic stimulation (TMS), with an inter-stimulus interval of 25 ms (PAS25) was also done. Before and after the motor tasks and PAS25, TMS was applied to the M1. None of the four tasks showed any temporary changes in behavior, meaning no learning occurred. Motor-evoked potential (MEP) amplitude increased only after the FG and it exhibited a positive correlation with the MEP increase after PAS25, suggesting that FG and PAS25 share at least similar plasticity mechanisms in the M1. Resting motor threshold decreased only after FG, suggesting that FG would also be associated with the membrane depolarization of M1 neurons. These results suggest a task-dependent plasticity from the synergistic effect of forceful muscle activity and of setting a goal of keeping the activity level constant.